2022
DOI: 10.1039/d2gc00573e
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling agro-industrial blueberry waste into platform chemicals and structured materials for application in marine environments

Abstract: Blueberries pruning waste (BPw), sourced as residues from agroforestry operations in Chile, were used to produce added-value products, including platform chemicals and materials. A BPw fractionation is implemented by using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The observations of survival and growth of coral fragments on these CS materials suggest possible uses as substrates for coral growth to be tested in the future at a larger scale, monitoring the kinetics of ions diffusion and degradation. Finally, CS was fixed with biopolymer filaments, [ 18 ] on an electrolytic coral restoration structure on the Cozumel coast (Mexico, August 8th to September 29th, 2021). Observations of low macroalgae covering CS in both wet lab and oceanic conditions suggested that the MCM might have contributed to the inhibition of macroalgae settlement and growth, contributing to coral colony fitness and health, particularly in nutrient‐rich waters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations of survival and growth of coral fragments on these CS materials suggest possible uses as substrates for coral growth to be tested in the future at a larger scale, monitoring the kinetics of ions diffusion and degradation. Finally, CS was fixed with biopolymer filaments, [ 18 ] on an electrolytic coral restoration structure on the Cozumel coast (Mexico, August 8th to September 29th, 2021). Observations of low macroalgae covering CS in both wet lab and oceanic conditions suggested that the MCM might have contributed to the inhibition of macroalgae settlement and growth, contributing to coral colony fitness and health, particularly in nutrient‐rich waters.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Within this latter context, cellulose mineralization offers an unprecedented opportunity for CO 2 removal and storage, for instance, in building materials. Cellulose a biopolymer that can be sourced from plants and biomass residuals, [17,18] has been reported for uses in advanced materials and energy-efficient construction. [19,20] Importantly, using mineralized cellulose as a building matrix may add new functionalities and properties to materials such as cement, [15] ceramic materials, [21] or even coral reef stones, [18,22] which are subjects of the present work.…”
Section: Introductionmentioning
confidence: 99%
“…31 Every sample was measured in three different positions, and the deconvolution and parameter calculation was performed following a reported procedure. 35 The degree of orientation and the Herman orientation factor were determined (Table 1). 31 A degree of orientation of 1 means perfect alignment of the bers (crystallites) to the long axis of the ber, while 0 means isotropic ber distribution.…”
Section: Waxs Measurementsmentioning
confidence: 99%
“…To overcome such burdens, large-scale fiber processing requires new production routes with low operational cost and environmental impact (Ministry of Economic Affairs and Employment of Finland, 2017). In this sense, there is a demand to shift to sustainable and circular processes (Hildebrandt et al, 2021), which have opened an opportunity for materials derived from cellulose, which can be sourced from wood, biomass, and agricultural waste (Isikgor & Becer, 2015;Melero et al, 2012;Oliveira et al, 2016;Reyes, Pacheco, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%